Feasibility research and suggestions of spectrum sharing - HOUYuzhe Z (Dianxin kexue)
With the advancement of information and industry strategies,5G technologies,and mobile internet,scarcity of radio spectrum resources highlighted again.Spectrum sharing provides a solution to the problem of spectrum scarcity.It is currently and actively under research by the international mainstream countries.Based on the analysis of domestic and international spectrum sharing research and application,the purposes and challenges of the spectrum sharing were further discussed,feasibility assessment framework for spectrum sharing was provided,and some suggestions were proposed to promote the implementation of spectrum sharing.